The European charter of fundamental rights: A changed political opportunity structure and its dogmatic consequences - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
The European Community is about to enlarge its de facto constitution by a fundamental rights charter. It is intended to become legally binding, at least in the long run. If it is, it will profoundly change the political opportunity structure between the Community and its Member States, among the Member States, among the organs of the Community and in relation to outside political actors. When assessing the new opportunities, one has to keep in mind the weak democratic legitimation of European policy making and its multi-level character. The article sketches the foreseeable effects and draws consequences from these insights for the dogmatics of the new fundamental rights, their relation to (other) primary Community law and to other fundamental rights codes. It ends with a view to open flanks that cannot be closed by the dogmatics of the freedoms themselves, but call for an appropriate design of the institutional framework.
Keywords: 330